Inhibition of PEDV viral entry upon blocking N-glycan elaboration - Zhao, Yong; Tang, Tao; Zhao, Wenchang; Fu, Weiguang; Li, Tao (Virology (New York, N.Y.), 2024)
Porcine Epidemic Diarrhea Virus (PEDV) poses a significant threat to the global swine industry, demanding a thorough understanding of its cellular invasion mechanism for effective interventions. This study meticulously investigates the impact of O- and N-linked glycans on PEDV proteins and host cell interaction, shedding light on their influence on the virus's invasion process. Utilizing CRISPR-Cas9 technology to inhibit cell surface O- and N-linked glycan synthesis demonstrated no discernible impact on virus infection. However, progeny PEDV strains lacking these glycans exhibited a minor effect of O-linked glycans on virus infection. Conversely, a notable 40% reduction in infectivity was observed when the virus surface lacked N-linked glycans, emphasizing their pivotal role in facilitating virus recognition and binding to host cells. Additionally, inhibition studies utilizing kifunensine, a natural glycosidase I inhibitor, reaffirmed the significant role of N-linked glycans in virus infection. Inhibiting N-linked glycan synthesis with kifunensine substantially decreased virus entry into cells and potentially influenced spike protein expression. Assessment of the stability and recovery potential of N-linked glycan-deficient strains underscored the critical importance of N-glycans at various stages of the virus lifecycle. In vivo experiments infecting piglets with N-glycan-deficient strains exhibited milder clinical symptoms, reduced virus excretion, and less severe pathological lesions compared to conventional strains. These findings offer promising translational applications, proposing N-glycosylation inhibitors as potential therapeutic interventions against PEDV. The utilization of these inhibitors might mitigate virus invasion and disease transmission, providing avenues for effective antiviral strategies and vaccine development. Nonetheless, further research is warranted to elucidate the precise mechanisms of N-linked glycans in PEDV infection for comprehensive clinical applications.